EMBRYOLOGICAL DEVELOPMENT OF Tetranychus cinnabarinus (Boisduval) (ACARI: TETRANYCHIDAE), PEST OF CARNATION (Dianthus caryophyllus L.) - ROSERO, LILIANA; TORRES-T., MARIELA; ACOSTA-G., ALFREDO (Revista Colombiana de Entomología, 1990)
The pursuit of several stages in the embryology of carmine spider mite Tetranychus cinnabarinus (Boisduval) (Acari: Tetranychidae) was realized on sectionated eggs by optic and electronic microscopy. The egg of this species is the centrolecithal type, spheric in form, its surface is soft and its consistency smooth and flexible. lt's envelope results of three layers or strata ultrastructurally well-differentiated each one. The eggdiameter varíes from 125 to 150 The initial development stage is the combination cleavage, at last of which, it is formed, the blastoderm, a single layer of cells covering completely the yolk, is formed. The development process continues then in the 24-34 hours egg with the germ band formation by cell proliferation of blastodderm. The segmentation (metamerization) to germ band begins at 36 hours and results in the formation of six prosomatic segments at 60 hours. These prosomatic segments give origin to the definitive larval appendages, at 96 hours. The central nervous system is totally formed about 72 hours meanwhile the germ band retirement. In the 96 hours developing egg, it is possible to observe the embryonic respiratory system through the egg envelope. The digestive and excretory system formation is shared by endodermic cells of the posterior proliferation and vitellophags cells. In the mouthparts, formation intervenes the two former appendages pairs. The musculature is completely formed in the 144 hours egg, with main muscle groups well differentiate. The structures as ocular spots and tegument, of endodermic origin, were only observed to 144 hours. The total egg stadium takes 168 hours to be completed.